Epidemiological aspects and spatial patterns of human visceral leishmaniasis in Brazil - Graepp-Fontoura, Iolanda; Soeiro Barbosa, David; Nascimento, Luiz Fernando Costa [UNESP]; Fontoura, Volmar Morais; Ferreira, Adriana Gomes Nogueira; Arrais Sampaio Santos, Francisca Aline; Sousa, Benedito Salazar; Santos, Floriacy Stabnow; Santos-Neto, Marcelino; Dos Santos, Leonardo Hunaldo; Abreu-Silva, Ana Lúcia (Cambridge University Press (CUP), 2020)
Human visceral leishmaniasis (HVL) cases are important public health problems due to their zoonotic aspect, with high rates of morbidity and mortality in Brazil. The aim of this this study was to identify spatial patterns in both rates of HVL cases in Brazilian states during the period from 2006 to 2015. This is an ecological study, using geoprocessing tools to create choropleth maps, based on secondary data from open access platforms, to identify priority areas for control actions of the disease. Data were collected in 2017 and analysed according to the global and local Moran's I, using TerraView 4.2.2 software. Similar clusters were observed in neighbouring municipalities in thematic maps of HVL, suggesting spatial similarity in the distribution of the disease in humans mainly in the North and Northeast Regions, which concentrate the states with the highest rates of HVL. Heterogeneous spatial patterns were observed in the distribution of HVL, which show municipalities that need higher priority in the intensification of disease surveillance and control strategies.
Keywords: Brazil; human visceral leishmaniasis; leishmaniasis; spatial analysis